2017
DOI: 10.1002/suco.201600005
|View full text |Cite
|
Sign up to set email alerts
|

Basic parameters test and 3D modeling of bond between high‐strength concrete and ribbed steel bar after elevated temperatures

Abstract: This paper presents basic parameters test and an efficient numerical model for the bond between reinforcing bars and concrete after elevated temperatures. The chemical adhesive and friction coefficient are measured by self‐designed setups, and the variation law of the parameters is summarized. In the 3D modeling, bar‐to‐concrete interface has been modeled by means of an explicit discretization of the bar ribs. Surface‐to‐surface contact pair elements are employed for the interface, and the tangential contact b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Since different surfaces with various roughness are in contact at the actual condition of the rebar-concrete interface, it is too complicated to consider all frictional coefficients during slip in the numerical modelling. Based on previous experimental investigations ( [73] and [72]), the friction coefficient varies from 0.52 to 1.4. As shown in section 4.1.3.4 (Figure 4-20), comparing numerical results of the proposed technique and experimental results showed that considering the coefficient of friction μ=1 leads to the best results under different values of external pressure.…”
Section: External Pressure Effects On Local Bond-slip Behaviourmentioning
confidence: 99%
“…Since different surfaces with various roughness are in contact at the actual condition of the rebar-concrete interface, it is too complicated to consider all frictional coefficients during slip in the numerical modelling. Based on previous experimental investigations ( [73] and [72]), the friction coefficient varies from 0.52 to 1.4. As shown in section 4.1.3.4 (Figure 4-20), comparing numerical results of the proposed technique and experimental results showed that considering the coefficient of friction μ=1 leads to the best results under different values of external pressure.…”
Section: External Pressure Effects On Local Bond-slip Behaviourmentioning
confidence: 99%
“…Since different surfaces with various roughness are in contact at the actual condition of the rebar-concrete interface, it is too complicated to consider all frictional coefficients during slip in the numerical modelling. Based on previous experimental investigations ( [73] and [72]), the friction coefficient varies from 0.52 to 1.4. As shown in section 4.1.3.4 (Figure 4-20), comparing numerical results of the proposed technique and experimental results showed that considering the coefficient of friction μ=1 leads to the best results under different values of external pressure.…”
Section: External Pressure Effects On Local Bond-slip Behaviourmentioning
confidence: 99%
“…Nowadays RC reinforcing bars are produced with a special thermal treatment process usually called Tempcore . It is based on a controlled, three‐stage cooling of a bar just after it leaves the last stand of hot‐rolling mill.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments, which can be useful for assessment of structures after fire, are also present in the literature . describe tests of residual yield strength of bars that were heated to a high temperature and allowed to slowly cool down in air . examined the reduction of bond strength between concrete and steel as the result of high temperature .…”
Section: Introductionmentioning
confidence: 99%